Pengaruh Metode Pembelajaran Mind Map (Peta Pikiran) Terhadap Motivasi Belajar Matematika Siswa Kelas Vii Pada Materi Pokok Segitiga Dan Segiempat Di Mts.Qamarul Huda Badaruddin Bagu Tahun Pelajaran 2022/2023 - Fadli, Saiful; Lalu Butsiawan Dasarja (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2023)
This study aims to obtain the results of the mind map learning method on the motivation to learn mathematics in grade VII students on the subject matter of triangles and quadrilaterals. Motivation to learn is important and needs to be known by every teacher in his role, namely being able to foster enthusiasm, feel happy and enthusiastic about learning for students. Motivation is related to a number of students' involvement in class activities such as encouragement to do something based on certain goals, certain habits and desires. The existence of several problems encountered during observations and interviews provoked the researcher's desire to develop student motivation, especially in mathematics. One of them is by increasing students' creativity in summarizing mathematics subject matter with the mind map technique. Associated with student completeness in the Even semester grades students encourage researchers to want to improve student achievement and student motivation in mathematics. Therefore, researchers are encouraged to find out more about "The Influence of the Use of the Mind Map Technique on the Mathematics Learning Motivation of Grade VII MTs Students. Qamarul Huda Bagu Academic Year 2020-2023.